Budget Performance in the Tourism Program During the National Economic Recovery Period 2020-2022 at the Ministry of Tourism and Creative Economy - Debby Marseilla Amahorseya (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the realization and impact of the National Economic Recovery (PEN) budget on Indonesia’s tourism sector during the COVID-19 pandemic from 2020 to 2022. Findings indicate that PEN funds, distributed directly to stakeholders including health workers, tourism operators, and creative economy participants support initiatives like CHSE certification and local product promotion. These efforts have bolstered tourism recovery, increasing visitor confidence and supporting local businesses. Key destinations like Bali and Borobudur experienced revitalization. The study also underscores the importance of transparency in financial management, with audits and public disclosures enhancing stakeholder trust.